Modelling of the static indentation of honeycomb core sandwichs with metallic skins - Aminanda, Yulfian; Castanie, Bruno; barrau, jean-jacques; thevenet, pascal (EDP Science, 2005)
In this research, the study and modelling of the low velocity/low energy impact on sandwich structures with metallic skins is carried out by considering that the static/dynamic equivalence is valid for the structures and ranges of impact studied. A phenomenological study of the behaviour of honeycomb subjected to crushing is completed first, making it possible to propose a simple analytical model based on a uniform compression test. This model is used to create a good simulation of honeycomb structures in indentation for various indentor geometries. A finite element model can then be made based on nonlinear springs and which correlates with the contact laws of static indentation tests of metal-skins NomexTM honeycomb sandwich structures.